2003
DOI: 10.1159/000076297
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species chromosome painting in the Perissodactyla: delimitation of homologous regions in Burchell’s zebra <i>(Equus burchellii)</i> and the white <i>(Ceratotherium simum)</i> and black rhinoceros <i>(Diceros bicornis)</i>

Abstract: Conserved chromosomal segments in the black rhinoceros, Diceros bicornis (DBI, 2n = 84), and its African sister-species the white rhinoceros, Ceratotherium simum (CSI, 2n = 82), were detected using Burchell’s zebra (Equus burchellii, EBU, 2n = 44) chromosome-specific painting probes supplemented by a subset of those developed for the horse (Equus caballus, ECA, 2n = 64). In total 41 and 42 conserved autosomal segments were identified in C. simum and D. bicornis respectively. Only 21 rearrangements (20 fissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Human homologies that were not found in these experiments but that are inferred from previously published data ) are indicated by circles. segments in at least one of the three perissodactyl families; the acrocentric chromosome ECA 15 is disrupted into two segments in rhinoceroses; similarly, the fragmentation of ECA 4 in DBI accounts for the difference in 2n between CSI and DBI, as was previously demonstrated (Trifonov et al 2003, Robinson et al 2005. In total, the 31 ECA chromosomes delimit 42 evolutionarily conserved segments in Perissodactyla (if we discard the ECA4/31 inversion in donkey chromosome 1, Yang et al 2004); 74 combinations of evolutionarily conserved ECA segments are also revealed (Supplementary Table S1).…”
Section: Multidirectional Chromosome Painting Between Perissodactyl Ssupporting
confidence: 68%
See 3 more Smart Citations
“…Human homologies that were not found in these experiments but that are inferred from previously published data ) are indicated by circles. segments in at least one of the three perissodactyl families; the acrocentric chromosome ECA 15 is disrupted into two segments in rhinoceroses; similarly, the fragmentation of ECA 4 in DBI accounts for the difference in 2n between CSI and DBI, as was previously demonstrated (Trifonov et al 2003, Robinson et al 2005. In total, the 31 ECA chromosomes delimit 42 evolutionarily conserved segments in Perissodactyla (if we discard the ECA4/31 inversion in donkey chromosome 1, Yang et al 2004); 74 combinations of evolutionarily conserved ECA segments are also revealed (Supplementary Table S1).…”
Section: Multidirectional Chromosome Painting Between Perissodactyl Ssupporting
confidence: 68%
“…The chromosomes of white and black rhinoceroses were arranged according to Trifonov et al (2003), while the chromosomes of Malayan tapir and the first 15Y20 large chromosomal pairs of the New World tapirs were arranged according to GTG-banded karyotypes published by Houck et al (2000). The remaining smaller autosomes of the New World tapirs were arranged largely according to their size, from the largest to the smallest.…”
Section: Karyotypingmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, E. burchelli probes have been employed for the comparison of karyotypes in some members of rhinoceros (Trifonov et al 2003), which belong to the same order as Equidae.…”
Section: Introductionmentioning
confidence: 99%